Coking and carbon deposition prevention coating for acetylene cracking furnace and preparation method of coking and carbon deposition prevention coating

By using a coking carbon deposit coating made of a variety of high-temperature resistant materials and sealing agents in the acetylene cracking furnace, the problem of carbon black accumulation in the inner wall of the acetylene cracking furnace is solved, and higher operating stability and lower Running cost.

CN119410179APending Publication Date: 2025-02-11WANHUA CHEM GRP CO LTD +1
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202411778353.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-05
Publication Date
2025-02-11

AI Technical Summary

Technical Problem

The acetylene cracking furnace produces coking carbon deposits at high temperatures, resulting in the accumulation of carbon black on the inner wall of the reactor, affecting the heat exchange efficiency, and the existing coating cannot effectively solve this problem.

Method used

A coking-resistant carbon coating with high temperature resistance materials such as silicon oxide, zirconium oxide, alumina, silicon carbide and silicon nitride is used, and a silicon sol or silane is used as a sealing agent to form a compact through plasma spraying and high temperature treatment. Wear-resistant coating.

Benefits of technology

This coating can effectively prevent coking carbon deposits in the acetylene cracking furnace, reduce manual carbon scraping operations, reduce natural gas venting risks, improve furnace stability and reduce operating costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005172106510000021
    Figure BDA0005172106510000021
  • Figure BDA0005172106510000061
    Figure BDA0005172106510000061
  • Figure BDA0005172106510000071
    Figure BDA0005172106510000071
Patent Text Reader

Abstract

The invention designs a coking and carbon deposition prevention coating for an acetylene cracking furnace, which takes high-temperature-resistant oxides such as silicon oxide, silicon carbide / tungsten carbide, zirconium oxide / aluminum oxide / chromium oxide, silicon nitride and the like as main raw materials, and uses silica sol or silane as a hole sealing agent. The coating is compact and smooth after being completed, has the advantages of high temperature resistance, wear resistance, chemical inertness and the like, and solves the problems of coking and carbon deposition of the acetylene cracking furnace.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of high-temperature anti-coking and carbon deposition coatings, and in particular to an anti-coking and carbon deposition coating for an acetylene cracking furnace and a preparation method thereof. Background Art

[0002] The process of producing acetylene by cracking natural gas utilizes the cracking reaction of natural gas at high temperature to generate acetylene. However, during the cracking reaction, the oxygen content and cracking temperature control will cause the reaction to move. The by-product carbon black will adhere to the wall of the cracking furnace. As time goes by, the thickness of the carbon black increases, affecting the heat exchange between the reactor and the circulating water in the jacket, thereby causing the temperature to rise, which may cause early ignition.

[0003] In order to solve the problem of carbon black accumulation on the inner wall of the cracking furnace affecting heat exchange, a carbon scraping rod is designed in the cracking furnace. Manual carbon scraping is performed once every 1 hour of operation of the cracking furnace. The carbon scraping process is completely operated by personnel. The running trajectory of the carbon scraping rod in the furnace may affect the internal flow field or temperature field, resulting in an increase in local oxygen content, and eventually causing the flame in the furnace to go out and the natural gas to be vented, resulting in economic losses.

[0004] At present, no research has been conducted in the industry on this situation. In order to improve the operating stability of acetylene cracking furnaces, reduce natural gas venting, and reduce manual carbon scraping operations, a high-temperature resistant and effectively anti-coking and carbon deposition coating has been developed. This is of great significance for effectively solving the coking and carbon deposition in acetylene cracking furnaces, ensuring safe, stable and economical operation, and reducing manual operations.

[0005] The Chinese patent document with the patent publication number CN118185419A discloses an anti-coking coating for the surface of the casting material of the combustion chamber of a garbage incinerator, which is composed of the following raw materials in weight percentage: 15-25% of high-purity large-crystal silicon carbide powder, 15-25% of fused zirconium oxide powder, 10-15% of chromium oxide fine powder, 20-25% of high-purity zirconium boride powder, 10-15% of aluminum oxide fine powder and 15-20% of a binder. The conditions for the coating to react and adhere to the high-temperature coke are reduced, and the casting material and the high-temperature coke are separated from each other. In addition, the high-purity large-crystal silicon carbide and high-purity zirconium boride are also non-oxide materials, which are not easy to react with oxide materials, further ensuring the effect that the coating and the gray coke do not adhere.

[0006] However, the above coating cannot solve the coking and carbon deposition problem in the acetylene cracking furnace. The coking mechanism is quite different. The acetylene cracking furnace has both chemical coking and carbon black physical adsorption processes. The coating surface is rough and there is no sealing agent. Although it can withstand high temperatures, it cannot solve the coking and carbon deposition problem in the cracking furnace based on the use conditions of the cracking furnace. Summary of the invention

[0007] In order to solve the above problems, the purpose of the present invention is to provide an anti-coking and carbon deposition wear-resistant coating and a preparation method. The coating prepared by the present invention has the characteristics of high-temperature anti-coking and carbon deposition, wear resistance and corrosion resistance.

[0008] The purpose of the present invention is to be achieved through the following technical solutions:

[0009] An anti-coking and carbon deposition coating for an acetylene cracking furnace, the coating comprising the following raw materials in parts by mass:

[0010]

[0011] In the present invention, the non-metallic oxide is silicon oxide;

[0012] In the present invention, the metal oxide includes one or more of zirconium oxide, yttrium oxide, aluminum oxide, and chromium oxide;

[0013] In the present invention, the carbide includes one or both of silicon carbide and tungsten carbide;

[0014] In the present invention, the nitride includes one or both of silicon nitride and boron nitride.

[0015] In the present invention, the sealing agent is silica sol (SiO2 content 15-25%) or silane (including one or two of polysiloxane and polynitrogen silane, siloxane and / or polynitrogen silane are prepared as a 5-30% mixture, and the dispersion medium is water);

[0016] As a further optimization of the present invention, the zirconium oxide particle size is less than 200 μm, the silicon oxide particle size is less than 100 μm, the yttrium oxide particle size is less than 100 μm, the aluminum oxide particle size is less than 100 μm, the chromium oxide particle size is less than 200 microns, the silicon carbide particle size is less than 100 μm, the silicon nitride particle size is less than 100 μm, the tungsten carbide particle size is less than 100 μm, and the boron nitride particle size is less than 100 μm.

[0017] The present invention also provides a method for preparing an anti-coking and carbon deposition coating for an acetylene cracking furnace, the steps of which are as follows:

[0018] (1) Weighing each material according to the composition of each raw material of the coating, and mixing the weighed materials except the sealing agent uniformly to obtain a coating mixture; the mixing method can be selected from ball milling, direct mechanical stirring of solid powder, heating liquid slurry stirring and then drying, etc., but is not limited to any one of the mixing methods;

[0019] (2) Clean the surface of metal materials, requiring the roughness to be ≤5μm, and use solvents to clean surface oil stains, etc.;

[0020] (3) Spraying the prepared coating mixture onto the surface of the metal material by plasma spraying, and controlling the spraying thickness to 100-1000 μm;

[0021] (4) Apply a sealant to the sprayed coating surface and then treat it at a high temperature of 100-1000°C for 1-10 hours;

[0022] (5) Repeat the previous step 1-50 times to complete the coating process.

[0023] In the present invention, as a further optimization, the finished coating is polished to ensure that the surface roughness is 0.1-5 μm, so as to obtain an anti-coking and carbon deposition coating.

[0024] The beneficial effects of the present invention are:

[0025] The coating of the present invention is composited with a variety of high temperature resistant materials and uses a Si-containing sealing agent to form a dense wear-resistant coating that can withstand high temperatures of 800-1200°C. The dense structure isolates the metal matrix material from the reaction materials, eliminating the chemical coking process.

[0026] Preferably, the surface is roughened to reduce the adsorption of carbon black and other cracking byproducts on the surface, and the coating is made of inert materials that do not react with the substances in the cracking furnace at high temperatures to ensure safety and reliability;

[0027] The present invention solves the coking and carbon deposition problems in the cracking furnace from the two aspects of chemical coking and material carbon deposition, which can significantly reduce the number of manual carbon scraping times, reduce the flameout of the cracking furnace caused by carbon scraping and lead to the venting of natural gas, reduce the operating cost, and improve the operating stability of the acetylene cracking furnace. DETAILED DESCRIPTION

[0028] In order to facilitate the understanding of the present invention, the present invention will be further described below in conjunction with examples. It should be understood that the following examples are only for a better understanding of the present invention and do not mean that the present invention is limited to the following examples.

[0029] Source of raw materials:

[0030] All raw materials of the present invention have no particular restrictions on their sources; among them, the particle size of zirconium oxide is less than 200 μm, the particle size of silicon oxide is less than 100 μm, the particle size of yttrium oxide is less than 100 μm, the particle size of aluminum oxide is less than 100 μm, the particle size of chromium oxide is less than 200 microns, the particle size of silicon carbide is less than 100 μm, the particle size of silicon nitride is less than 100 μm, the particle size of tungsten carbide is less than 100 μm, and the particle size of boron nitride is less than 100 μm.

[0031] Test performance of examples and comparative examples

[0032] Preparation of samples

[0033] The experimental specimens were prepared according to the following construction method, including the following steps:

[0034] Take a 20G steel plate with a plate size of 80*80*5mm, clean the sprayed surface, the roughness is required to be ≤5μm, and use acetone solvent to clean the surface oil, etc.;

[0035] Coating samples were prepared according to the methods of Examples 1-4 and Comparative Example 1.

[0036] Example 1

[0037] An anti-coking and carbon deposition coating for an acetylene cracking furnace is composed of the following raw materials in parts by weight: 10 parts by weight of silicon oxide, 45 parts by weight of zirconium oxide, 8 parts by weight of aluminum oxide, 2 parts by weight of yttrium oxide, 21 parts by weight of silicon carbide, and 16 parts by weight of silicon nitride; and 2 parts by weight of silica sol (divided into 14 parts for use), wherein the SiO2 content is 19%, which serves as a sealing agent.

[0038] The weighed materials except the silica sol are mixed by ball milling for 20 minutes to obtain a coating mixture;

[0039] Clean the sprayed surface, with a roughness of ≤5μm, and use acetone solvent to clean the surface oil stains, etc.;

[0040] Spray the prepared coating mixture onto the surface of the metal material by plasma spraying, and control the spraying thickness to 100-300μm;

[0041] Silica sol was brushed on the sprayed coating surface, and then treated at 240°C for 1 hour, and this operation was repeated 13 times;

[0042] The finished coating is polished to ensure the surface roughness is 3μm.

[0043] Example 2

[0044] An anti-coking and carbon deposition coating for an acetylene cracking furnace is composed of the following raw materials in parts by weight: 20 parts by weight of silicon oxide, 38 parts by weight of zirconium oxide, 13 parts by weight of chromium oxide, 1 part by weight of yttrium oxide, 15 parts by weight of silicon carbide, 18 parts by weight of silicon nitride, and 3 parts by weight of boron nitride; and 3 parts by weight of silica sol (divided into 21 parts), in which the SiO2 content is 15%, as a sealing agent.

[0045] The weighed materials except the silica sol are mixed by ball milling and mechanically stirred for 60 minutes to obtain a coating mixture;

[0046] Clean the sprayed surface, with a roughness of ≤5μm, and use acetone solvent to clean the surface oil stains, etc.;

[0047] Spray the prepared coating mixture onto the surface of the metal material by plasma spraying, and control the spraying thickness to 200-400μm;

[0048] Use silica sol to brush on the sprayed coating surface, then treat it at 120℃ for 4h, and repeat this operation 20 times;

[0049] The finished coating is polished to ensure the surface roughness is 2μm.

[0050] Example 3

[0051] An anti-coking and carbon deposition coating for an acetylene cracking furnace is composed of the following raw materials in parts by weight: 30 parts by weight of silicon oxide, 40 parts by weight of chromium oxide, 0.5 parts by weight of yttrium oxide, 20 parts by weight of silicon carbide, and 20 parts by weight of silicon nitride; and 3 parts by weight (divided into 16 parts) of a polynitrogen silane solution, wherein the content of the polynitrogen silane is 15%, which is used as a sealing agent.

[0052] The weighed materials of the polynitrogen-free silane solution were mixed by ball milling and mechanically stirred for 60 minutes to obtain a coating mixture;

[0053] Clean the sprayed surface, with a roughness of ≤5μm, and use acetone solvent to clean the surface oil stains, etc.;

[0054] Spray the prepared coating mixture onto the surface of the metal material by plasma spraying, and control the spraying thickness to 200-300μm;

[0055] Use polynitrogen silane solution to brush the sprayed coating surface, then treat it at 700℃ for 3h, and repeat this operation 15 times;

[0056] The finished coating is polished to ensure the surface roughness is 1μm.

[0057] Example 4

[0058] The invention discloses an anti-coking and carbon deposition coating for an acetylene cracking furnace, which is composed of the following raw materials in parts by weight: 15 parts by weight of silicon oxide, 29 parts by weight of zirconium oxide, 30 parts by weight of chromium oxide, 1.5 parts by weight of yttrium oxide, 20 parts by weight of silicon carbide, and 22 parts by weight of boron nitride; and 5 parts by weight (divided into 11 parts) of silica sol, in which the SiO2 content is 20%, which is used as a sealing agent.

[0059] The weighed materials except the silica sol are mixed evenly. The mixing method can be selected to be a ball mill mixing method for mixing, and mechanically stirred for 20 minutes to obtain a coating mixture;

[0060] Clean the sprayed surface, the roughness is required to be ≤5μm, and use acetone solvent to clean the surface oil, etc.;

[0061] Spray the prepared coating mixture onto the surface of the metal material by plasma spraying, and control the spraying thickness to 300-500μm;

[0062] Use silica sol to brush on the sprayed coating surface, then treat it at 400℃ for 2h, and repeat this operation 10 times;

[0063] The finished coating is polished to ensure the surface roughness is 2μm.

[0064] Comparative Example 1

[0065] A coating for preventing coking and carbon deposition in an acetylene cracking furnace, wherein silica sol is not used to seal the pores on the coating surface, and no grinding treatment is performed, and the remaining components, proportions and preparation methods are completely consistent with those in Example 1.

[0066] Experimental Results

[0067] The experimental samples prepared in Examples 1-4 and Comparative Example 1 were tested to observe the anti-coking performance of the coating (device hanging test, 1 month), corrosion resistance (mixed coke / coating sample of acetylene cracking device, calcined at 800°C), thermal shock (800°C water-cooled thermal shock, refer to GB / T 4653-1984), and wear resistance (reciprocating wear test, load 2kg, 1000 times). No less than five test samples for each performance were tested, and the maximum and minimum values ​​were removed. The test results were averaged and compared with the carbon coking data of the carbon steel material of the cracking furnace of the device and the wear resistance of the material; the specific results are shown in Table 1.

[0068] Table 1 Performance test results

[0069]

[0070]

[0071] It is easy to understand that the above embodiments are only examples for clear explanation and do not mean that the present invention is limited thereto. For ordinary technicians in the relevant field, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived from this are still within the protection scope of the present invention.

Claims

1. An anti-coking and carbon deposition coating for an acetylene cracking furnace, the coating comprising the following raw materials in parts by weight:

2. The anti-coking and carbon deposition coating according to claim 1, wherein: The non-metallic oxide is silicon oxide; preferably, the particle size of the silicon oxide is less than 100 μm.

3. The anti-coking and carbon deposition coating according to claim 1, wherein: The metal oxide includes one or more of zirconium oxide, yttrium oxide, aluminum oxide, and chromium oxide; preferably, the particle size of zirconium oxide is less than 200 μm, the particle size of yttrium oxide is less than 100 μm, the particle size of aluminum oxide is less than 100 μm, and the particle size of chromium oxide is less than 200 μm.

4. The anti-coking and carbon deposition coating according to claim 1, wherein: The carbide includes one or both of silicon carbide and tungsten carbide; preferably, the particle size of silicon carbide is less than 100 μm, and the particle size of tungsten carbide is less than 100 μm.

5. The anti-coking and carbon deposition coating according to claim 1, wherein: The nitride includes one or both of silicon nitride and boron nitride; preferably, the particle size of silicon nitride is less than 100 μm, and the particle size of boron nitride is less than 100 μm.

6. The anti-coking and carbon deposition coating according to claim 1, wherein: The sealing agent is silica sol (SiO2 content 15-25%) or silane (preferably one or two of polysiloxane and polynitrogen silane, siloxane and / or polynitrogen silane are prepared as a 5-30% mixture, and the dispersion medium is water).

7. The method for preparing the anti-coking and carbon deposition coating according to any one of claims 1 to 6, comprising: (1) Weighing various materials, and evenly mixing the weighed materials except the sealing agent to obtain a coating mixture; (2) Clean the surface of the metal material, with a roughness of ≤5μm, and use a solvent to remove surface oil stains; (3) Spraying the prepared coating mixture onto the surface of the metal material by plasma spraying; (4) Apply a sealant to the sprayed coating surface and then treat it at a high temperature of 100-1000°C for 1-10 hours; (5) Repeat the previous step 1-50 times to complete the coating process.

8. The method according to claim 7, wherein: In step (3), the spraying thickness is controlled to be 100-1000 μm.

9. The method according to claim 7, wherein: The finished coating is polished to ensure that the surface roughness is 0.1-5μm, thus obtaining an anti-coking and carbon deposition coating.

Citation Information

Patent Citations

  • Anti-coking coating for surface of castable of combustion chamber of garbage incinerator and preparation method of anti-coking coating

    CN118185419A

  • Coke oven ascending tube enameled brick and preparation method thereof

    CN102603338A

  • Nanocomposite and nanocomposite furnace tube

    CN103965666A

  • High-temperature-resistant and corrosion-resistant nano self-cleaning coating and preparation method and application thereof

    CN106543779A

  • Anti-coking and anti-slagging coating material for four tubes of boiler and preparation method of anti-coking and anti-slagging coating material

    CN109486414A